2018
DOI: 10.1177/1687814018784410
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of heat transfer enhancement in the entrance region for low-pressure gaseous laminar pipe flows using Al2O3–air nanofluid

Abstract: The gaseous low-pressure nanofluid flow of a steady-state two-dimensional laminar forced convection heat transfer in the entrance region of pipes is numerically investigated. Such flows are of interest for many engineering applications like the nuclear reactor and electronic equipment cooling, heat exchangers, and many others. Physical parameters considered in this study are Reynolds number (Re), Prandtl number (Pr), nanosolid particles volume fraction (f), Knudsen number (Kn), and the aspect ratio (AR). These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In addition, the correlation for the total entropy generation among all the investigated parameters is proposed. Finally, Al-Kouz et al [80] conducted a numerical study to investigate heat transfer characteristics in the entrance region of laminar rarefied air/Al 2 O 3 flow in pipes. The effects of the aspect ratio, Knudsen number, Reynolds number and the nanosolid particle volume fraction on the heat transfer characteristics were presented, and a correlation of Nusselt number among all the investigated parameters is introduced.…”
Section: Thermal Applications Of Hybrid Nanofluidsmentioning
confidence: 99%
“…In addition, the correlation for the total entropy generation among all the investigated parameters is proposed. Finally, Al-Kouz et al [80] conducted a numerical study to investigate heat transfer characteristics in the entrance region of laminar rarefied air/Al 2 O 3 flow in pipes. The effects of the aspect ratio, Knudsen number, Reynolds number and the nanosolid particle volume fraction on the heat transfer characteristics were presented, and a correlation of Nusselt number among all the investigated parameters is introduced.…”
Section: Thermal Applications Of Hybrid Nanofluidsmentioning
confidence: 99%
“…Moreover, they proposed a correlation of Nusselt number among all the parameters investigated in their study. In addition, Al‐Kouz et al investigated numerically the heat transfer enhancement in the entrance region for low‐pressure gaseous laminar pipe flows using air‐Al 2 O 3 nanofluid; they concluded that as Reynolds number, volume fraction of the nanosolid particles, and Prandtl number increase, then the average Nusselt number increases. In addition, they found out that as the aspect ratio and Knudsen number increase, then the average Nusselt number decreases.…”
Section: Model Theory and Relevant Equationsmentioning
confidence: 99%
“…Hisham et al [28] examined the flow of two-phase Maxwell fluids between parallel plates. Moreover, and due to the importance of nano/hybrid nanofluids in the enhancement of heat transfer, many researchers have investigated the impact of such fluids along with other physical parameters such as porous media, magnetohydrodynamics, rarefaction effects, and different geometries on the heat transfer [29][30][31][32][33][34][35][36][37][38][39][40][41]. The heat and mass transfer in three-layered channels was studied by Umavathi and Hemavathi [42].…”
Section: Introductionmentioning
confidence: 99%